MEASURING OF X-RAY SOURCE SIZE BY USING COMPOUND REFRACTIVE X-RAY LENS - Yu. V. Dudchik (Приборы и методы измерений, 2015)
Compound refractive lens was used for measuring size of 2-3 beamline Standford synchrotron radiation source and a size of microfocus X-ray tube. X-ray beam from the source was focused by the lens and parameters of the beam at image plane were measured. Scanning diaphragm and X-ray CCD-camera were used for measuring X-ray beam. It was found that the vertical size of synchrotron source is equal to 0,6 mm and the size of the X-ray tube focal spot is equal to 60 micrometers.